The interpretation of the legal obligation of a subject keeping an account of dematerialized securities in light of article 9118 of the Code of Civil Procedure – an analysis of the prohibition on enforcing a debtor’s disposition - Skibiński, Oskar (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The article is devoted to a semantic analysis of the prohibition on executing a disposition which is imposed on a debtor who appears in an enforcement proceeding as a subject keeping an account of a debtor’s dematerialized securities. The author analyzes the Code of Civil Procedure and Trading in the Financial Instruments Act in order to identify the legal meaning of the word ‚disposition’. To this end, the author compares the obtained results with the meaning of the word in the vernacular, colloquial language and the specific language used by brokers. Then, based on the findings, the author explains the functioning of the prohibition to execute a disposition in selected situations which may occur at that stage of the manner of enforcement. It has been found that the obliged entity follows the notification of seizure until the dispositions have been enforced. After that moment, for each disposition, a proper evaluation of the notification of seizure is not possible.